PELESTARIAN TARI KRETEK SEBAGAI KESENIAN KOTA KUDUS YANG DIKEMBANGKAN SANGGAR PURING SARI - Meilani, Annisa Sukma (Institut Seni Indonesia Surakarta, 2024)
Kretek dance is a new dance creation typical of Kudus Regency which lives, grows and develops in Kudus society. The Kretek dance was created in 1986 by an artist named Endang Tony and her husband Supriyadi. This dance depicts the process of making Kretek cigarettes and tells the story of the activities of cigarette workers, from selecting tobacco, tidying up cigarette sticks, to delivering them to the foreman for inspection. The Kretek dance has become a dance of pride for the people of Kudus and has become an iconic dance in the city of Kudus. This dance symbolizes that the city of Kudus is 'Kretek City', meaning the center of Kretek cigarette production, whether made traditionally by hand or modernly made by machines. The existence of Kretek dance cannot be separated from the role of Sanggar Puring Sari as one of the arts studios that preserves Kretek dance. This studio is in Barongan Village, Kota District, Kudus Regency. As a preserver of Kretek dance, Sanggar Puring Sari introduces Kretek dance in all its activities, especially during routine practice. This research is intended to describe the role of Sanggar Puring Sari Kudus Regency in preserving Kretek dance in Kudus Regency. Efforts to preserve the Kretek dance can be seen in tangible (visible) and intangible (invisible) ways. The research method uses qualitative research. Data collection techniques can be through observation, interviews and documentation. The data that has been obtained will be analyzed using data triangulation.